Syntax Processing. - Torrens, Vicenç (Cambridge Scholars Publisher, 2021)
This volume deals with research on the processing of a native language, second language learning, bilingualism, typical and impaired syntax processing. The articles presented here cover a number of linguistic phenomena, including passives, temporal concord, object pronouns, reflexives, embedded sentences, relative clauses, wh-movement, and binding theory. They also apply various experimental methods, such as eye tracking, reaction times, event-related potentials, picture selection tasks, sentence elicitation, pupillometry, and picture matching tasks. As such, this book details a number of the.